فلسفة الأخلاق ومعوقات التربية الأخلاقية في المجتمعات العربية المعاصرة - شروي, كريمة (جامعة الوادي - University of Eloued, 2015)
موضوع البحث عن فلسفة الأخلاق ومعوقات التربية الأخلاقية في المجتمعات المعاصرة، بينت فيه أهمية الأخلاق باعتباره ضرورة إنسانية ملحة إن على مستوى الأفراد أو الجماعات. حيث لابد من قواعد للتمييز بين الحق والباطل ، الخير والشر ، الصواب والخطأ ، حيث دور التربية الخلقية فيها عظيما حتى تمكن من التغلب على دواعي الهبوط والانحلال.ثم بينت جوانب الأخلاق في بعض الحضارات وأيضا في حضارة المسلمين. أما أهداف هذه الدراسة فتكمن في بيان المتغيرات الحديثة التي أصبحت عائقا أمام تحقيق التربية الأخلاقية . Conclusion: The title of the research is philosophy of morality and barriers of moral Education in contemporary societies .The research explained the importance of morality as an urgent necessity humanity at individual and group levels. So there should be rules to distinguish between truth and vicious ,good and evil ,true and false , for that the role of moral Education in those societies was so great for it overcome to all The reasons of decay and corruption , also the research Explained the affect of moral sides in civilizations specially muslim' civilizations but the aims of this study are clarifying the Modern changes which became hindrance for achieving moral Education.
مقال
Keywords: فلسفة الأخلاق، فلسفة الأخلاق الدينية،معوقات التربية الأخلاقية، الأسرة،التعليم،الإعلام، التقليد; The philosophy of ethics, philosophy and religious morality , obstacles to moral education , the family education , media , tradition